Construction of graphene oxide based mixed matrix membranes with CO2-philic sieving gas-transport channels through strong p-p Interactions - Cong, S.; Li, H.; Shen, X.; Wang, J.; Zhu, J.; Liu, Jian; Zhang, Y.; Van Der Bruggen, B. (R S C Publications, 2018)
© 2018 The Royal Society of Chemistry. Two-dimensional nanomaterials can be used to create innovative membranes with high permeability and selectivity, but precise manipulation of laminar stacking and the construction of ordered, CO2-philic molecular sieving channels remains a technological challenge. Here, gas separation membranes containing advanced CO2-philic nano-laminar clusters in the interlayer channels of graphene oxide (GO) were formed by the intercalation of an o-hydroxya porous organic polymers (POPs) into GO. POPs are phenolic azo-hierarchically mesoporous polymers; the azo group of POPs allows to reject N2, while the unreacted phenolic groups on the POP surface have a high CO2-philic and nanocephalic character. Beyond that, the introduced POPs could tailor the interlayer height of graphene oxide-assembled 2D nanochannels and feature an ordered structure of such graphene oxide nanosheets. Therefore, POP-GO may facilitate a superior CO2/N2separation performance for the membrane because of the synergetic effect of GO and POPs. The POP-GO membrane was found to have a high CO2permeability of 696 barrer and a CO2/N2ideal selectivity of 51.2, which is beyond Robeson's upper bound (2008). The d-spacing of graphene oxide after adjustment is approximately 3.5 Å according to a Density Functional Theory (DFT) simulation; this is between the dynamic radius of CO2and N2. This approach potentially offers the opportunity to precisely manipulate the d-spacing of graphene oxide through chemical bonds, which has potential for large-scale applications compared to conventional vacuum-assisted filtration.